2019
DOI: 10.1039/c9fo01423c
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-DAD-ESI-MS/MS screening of phytochemical compounds and the bioactive properties of different plant parts ofZizyphus lotus(L.) Desf.

Abstract: Zizyphus lotus L. (Desf.) presented flavonoids and secoiridoids derivatives and revealed to have cytotoxicity, anti-inflammatory and antimicrobial potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…In contrary, it exhibited a significant activity against MCF-7 cells. These findings can be due to the main bioactive compounds contained in Zls extract that may include flavonoids, tannins, alkaloids, terpenoids, and saponins as observed previously from other jujube species and from other part of Zizyphus lotus which showed a strong antiproliferative activity against HepG 2 and MCF-7 cells [21,74].…”
Section: Anti-proliferative Activity Of Zls Extractsupporting
confidence: 64%
See 1 more Smart Citation
“…In contrary, it exhibited a significant activity against MCF-7 cells. These findings can be due to the main bioactive compounds contained in Zls extract that may include flavonoids, tannins, alkaloids, terpenoids, and saponins as observed previously from other jujube species and from other part of Zizyphus lotus which showed a strong antiproliferative activity against HepG 2 and MCF-7 cells [21,74].…”
Section: Anti-proliferative Activity Of Zls Extractsupporting
confidence: 64%
“…The effective cytotoxicity toward hepatocellular HepG 2 and beast MCF-7 could be related to the presence of the some secondary metabolites, some of them are considered the major class of jujube polyphenols, represented from 89 to 94% of the total phenolic contents mainly flavan-3-ols such as monomer (as (-)-epicatechin, gallocatechin gallate, and (+)-catechin), dimer (procyanidine B2), and polymeric proanthocyanidins in Zls, which were applicated in the inhibition of cell proliferation in different cancer types [47]. Quercetin-3-O-rutinoside found in other parts of Z. lotus, which represents 50% of jujube flavonoids offers a plausible explanation of the observed cytotoxicity [74].…”
Section: Anti-proliferative Activity Of Zls Extractmentioning
confidence: 99%
“…According to EC 50 values on SH-SY5Y after 24 and 48 h of treatments, the dried root extracts of petroleum ether (DR-PEE) and dichloromethane (DR-DE) were selected and subsequent investigations were pursued. As reported by Rached et al [31], the root barks are always expressing a potent cytotoxic effect. Consistent cytotoxic activities were also observed by testing the root bark extracts on hepatocellular HepG2 (48.3 µg/mL), breast MCF-7 (74 µg/mL) and cervical HeLa (69 µg/mL) [31].…”
Section: Discussionmentioning
confidence: 72%
“…As reported by Rached et al [31], the root barks are always expressing a potent cytotoxic effect. Consistent cytotoxic activities were also observed by testing the root bark extracts on hepatocellular HepG2 (48.3 µg/mL), breast MCF-7 (74 µg/mL) and cervical HeLa (69 µg/mL) [31].…”
Section: Discussionmentioning
confidence: 72%
“…An increasing number of studies have identified a variety of bioactive secondary metabolites in Z. lotus, particularly phenolic compounds, which have been verified to be present in leaves, branches, and root and stem barks [7,8]. In addition, a vast number of biological properties have been attributed to Z. lotus polar extracts from different morphological parts, namely, antioxidant [8][9][10], antibacterial [8], anti-ulcerogenic [10], anti-inflammatory [5,8], analgesic [5], antidiabetic [9] and antispasmodic [11] activities.…”
Section: Introductionmentioning
confidence: 99%